JOURNAL OF FACTORS AFFECTING EARLY MARRIAGE IN WAIMAKAHA VILLAGE, KODI BALAGHAR DISTRICT, WEST SUMBA DISTRICT - Nurfajri; Asri Dewi Waheningtyas (Journal for Research in Public Health, 2022)
Early marriage socially will be the subject of discussion among teenagers and the community. Early marriage can result in teenagers dropping out of school so they lose the opportunity to study as a provision for the future. The life experience of those under 20 years old is usually not stable, if a woman at a young age of marriage becomes mentally unstable, then the fetus she contains will become an unwanted child. 2013). According to the United Nations Development Economic and Social Affairs, Indonesia was the 37th country with the highest number of early marriages in the world in 2007. For the ASEAN level, the rate of early marriage in Indonesia ranks second after Cambodia. group aged 10-14 years who are married, 1% have given birth to live children, 1% are divorced. Meanwhile, the incidence of young marriage in the group of adolescents aged 15-19 years who live in rural areas is 3.53% compared to 2.81% for urban adolescents (Zuraidah, 2016). From the point of view of obstetrical health, pregnancy at a young age poses the risk of complications that may occur to mother and child such as anemia, preeclampsia, eclampsia, abortion, premature labor, perinatal death, bleeding and obstetric surgery are more frequent than pregnancies in the age group of 20 years and over. . The World Health Organization (WHO) in 2015. stated that the MMR in the world is 216/100,000 KH, and in several countries including America 52/100,000 KH, Europe 16/100,000 KH while in Southeast Asia the mortality rate is still far different from some other countries, namely 164 /100,000 KH, covering Sri Lanka 30/100,000 KH, Thailand 20/100,000 KH and in Indonesia the MMR reached 126/100,000 KH, this figure is still far from the 2015 MDGs target of 102/100,000 KH. MMR is the main focus to reduce the percentage. lower the percentage. In 2018 in East Nusa Tenggara the maternal mortality rate was 142 cases. Meanwhile, maternal mortality in Southwest Sumba district reached 5 people (NTT Health Office, 2018). The number of infant mortality cases decreased from 33,278 in 2015 to 32,007 in 2016, and in 2017 there were 10,294 cases (Kemenkes RI, 2017). Infant mortality can result from a lack of awareness of maternal health. Many factors influence it, including mothers rarely checking their pregnancy with health workers, pregnant at a young age, the distance is too narrow, lack of nutritional intake for the mother and baby so that it can affect the incidence of LBW (Puspaningtyas et al, 2014). In 2012, the World Health Organization (WHO) reported the incidence of LBW in the world in the range of 2005-2010 was 15%. In South-East Asia the incidence of LBW reaches 24% and the highest is in India with a percentage of 28%. In Indonesia, according to the results of the Regional Health Research (Rikesdas) in 2013 it was stated that the percentage of LBW was 22.4% in East Nusa Tenggara (Dinkes Prov NTT 2018). Based on statistical data from the World Health Organization (WHO) in 2014, it showed that as many as 16 million births occurred to mothers aged 15-19 years or 11% of all births in the world, the majority (95%) occurring in developing countries. In Latin America and the Caribbean 29% of young women are married when they are 18 years old. The highest prevalence of early marriage cases in the world is in Nigeria (79%), Congo (74%), Afghanistan (54%), and Bangladesh (51%) (Ekawati, 2017). Talking about marriage, humans certainly need not only material and physical preparation, but also mental preparation. Related to this, there is a minimum age limit for a person to get married and this has been regulated in the Marriage Law of 1974 chapter II article 7 paragraph 1. In the article it is explained that marriage is only permitted if the man reaches the age of 19 years and the woman has reached the age of 16 years. Normal changes in Law No. 1 of 1974 concerning marriage reach the age limit for marriage, the improvement of norms reaches by increasing the minimum age for marriage for women. In this case, the minimum age for marriage for women is the same as the minimum marriage age for men which is 19 (nineteen) years. The said age limit is considered to have matured in mind and body to be able to carry out a marriage in order to realize the purpose of marriage properly without ending in divorce and obtaining healthy and quality offspring. It is also hoped that an increase in the age limit higher than 16 (sixteen) years for women to marry will result in a lower birth rate and reduce the risk of maternal and child mortality. In addition, the rights of children can be fulfilled so that they optimize. Based on the formulation of the problem above, the research objectives in this study are as follows. To find out and conclude the factors that cause early marriage for women in Waimakaha Village, Kodi Balaghar District, Southwest Sumba Regency. To find out and conclude the impact of early marriage on women in Waimakaha Village, Kodi Balaghar District, Southwest Sumba Regency.